Resurgence of destructive behavior following decreases in alternative reinforcement: A prospective analysis - Greer, Brian D.; Shahan, Timothy A.; Irwin Helvey, Casey; Fisher, Wayne W.; Mitteer, Daniel R.; Fuhrman, Ashley M. (Journal of applied behavior analysis, 2024)
Basic and retrospective translational research has shown that the magnitude of resurgence is determined by the size of the decrease in alternative reinforcement, with larger decreases producing more resurgence. However, this finding has not been evaluated prospectively with a clinical population. In Experiment 1, five participants experienced a fixed progression of reinforcement schedule‐thinning steps during treatment of their destructive behavior. Resurgence occurred infrequently across steps and participants, and when resurgence did occur, its clinical meaningfulness was often minimal. In Experiment 2, five new participants experienced these same schedule‐thinning steps but in a counterbalanced order. Resurgence occurred most often and was generally largest with larger decreases in alternative reinforcement programmed earlier in the evaluation. Large decreases in alternative reinforcement may be more problematic clinically when they occur earlier in treatment. Whether larger transitions can be recommended in the clinic following the success of smaller ones will require additional research.